Inadequate Revenue Threatens Afghanistan's Stability. Issue 1 (2nd April 2014) - Sternlieb, Steve
If Afghanistan is to maintain some semblance of stability in 2014 and beyond it must prepare for a substantial donor funding reduction and seek to grow its domestic revenue. Funding for the Afghan government's operating expenses as well as further development projects is heavily dependent on donor support. Unfortunately for Afghanistan, its fiscal position is eroding as domestic revenues decline, expenses rise, and donor aid falls. Security gains as well as public services and economic development are at risk due to this mismatch. Afghanistan's challenge in the coming years will be how to deal with this mismatch without fueling instability. It cannot simply assume that donor funding will continue to cover its funding gap. This paper assesses Afghanistan's deteriorating fiscal situation and concludes with some observations on what the Afghan government and the donor community must do, preferably in concert, to address it. It assumes that Afghanistan and the United States will ultimately sign a bilateral security agreement allowing a continued coalition military presence, without which the country's fiscal situation could rapidly deteriorate.